The Prevalence of Hyperpalatable Baby Foods and Exposure During Infancy: A Preliminary Investigation - Kong, Kai Ling; Fazzino, Tera L.; Rohde, Kaitlyn M.; Morris, Katherine S. (Frontiers in Psychology, 2021)
Objective: To characterize the prevalence of hyperpalatable foods (HPF) among baby foods in the U.S., and examine the prevalence of HPF exposure and consumption patterns among infants aged 9 – 15 months. Methods: Baby foods in the U.S. and those obtained from three 24-h dietary recalls of 147 infants were identified as HPF per previous publication. HPF exposure was defined as intake of any HPF during the 3-day measurement period. To determine extend of HFP consumption, % kcal intake from HPF was characterized. Results: Only 12% of baby foods were HPF; however, nearly all participants (>90%) consumed HPF, primarily through exposure to adult foods. Younger infants (<12 months) consumed 38% (standard deviation [SD]= 23.6%) of their daily food kcal from HPF and older infants (12 months) consumed 52% (SD = 16.4%) of daily food kcal from HPF. Most younger infants (68%) and older infants (88%) had repeated exposure to the same HPF across the measurement period. Conclusions: The prevalence of HPF among baby foods in the U.S. is low. However, almost all infants were exposed to HPF, and HPF comprised a substantial percentage of daily food kcal in infants’ diets. Findings highlight the transition to solid food consumption during complimentary feeding period is a critical time for early HPF exposure.